Electrically driven bidirectional shape memory polyimide composite fiber cloth and preparation method thereof
Patent Information
- Application Number
- CN202211723240.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-12-30
AI Technical Summary
[0005]本发明所要解决的技术问题是提供一种电驱动双向形状记忆聚酰亚胺复合纤维布及其制备方法,以克服现有技术中电驱动形状记忆聚合物形变小、制备复杂、导电、导热性不足、驱动电压高、形变回复慢的缺陷
[0029]本发明纤维布经纱中混纺有导电产热功能的纤维,作为导电第一组分,高效产热;一侧面通过激光雕刻出的导电通路作为导电第二组分,应注意到,经纱混纺其它纤维作为导电通路纬纱为聚酰亚胺纤维,此时,经纱平行排布,低含量导电纤维无规分布在纤维间,难以形成通路,通过表面激光雕刻出折叠线形导电通路,可将处于断路状态的第一组分导电通路连接,同时,对使用过程中导电纤维断裂导致的第一导电组分缺陷部分产生修补作用,大面积的碳化表面可将导电第一组分的产热传导至复合纤维布整体。导电第一组分与第二组分配合,实现导电通路的可设计性、导电-产热-导热的高效性、可制备方法简便。通电后,激光碳化的聚酰亚胺纤维产热,热塑性形状记忆聚酰亚胺薄膜受热后模量降低,进而触发储存有弯曲势能的聚酰亚胺纤维布,拉动样品回复永久形状,即,较为平展状态;断电后,激光碳化的聚酰亚胺纤维散热,形状记忆聚酰亚胺聚合物分子链弹性模量增大,拉动聚酰亚胺纤维布弯曲,样品回复临时卷曲形状,同时储存弯曲势能,重复此过程,样品经电驱动,实现在永久-临时形状间的循环转变。
Smart Images

Figure CN116587698B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of smart polymer materials and their preparation, and specifically relates to an electrically driven bidirectional shape memory polyimide composite fiber cloth and its preparation method. Background Technology
[0002] Shape memory polymers (SMPs) are a class of novel functional materials capable of sensing external stimuli such as heat, light, electricity, and magnetism, and responding according to a pre-defined path. With increasing human exploration of extreme environments such as space exploration, higher demands are being placed on shape memory polymers, such as superior weather resistance and excellent mechanical and thermal properties. Polyimide, due to its resistance to high / low temperatures, superior mechanical properties, radiation resistance, and dimensional stability, has greater application advantages than other polymers in special environments such as high / low temperature alternating fields and cosmic radiation. By controlling its structure, polyimide can be endowed with shape memory properties, achieving an organic combination of high performance and intelligence, enabling it to exert greater application advantages in high-tech fields such as lightweight composite materials, space-deployable structures, and thermal barrier applications.
[0003] Compared to traditional thermally driven methods, electrically driven shape memory polymer composites offer advantages such as remote controllability, rapid response, and high controllability, significantly expanding their application range. Currently, numerous studies report methods to achieve electro-drive by adding conductive fillers to the polymer matrix; however, these methods suffer from problems such as uneven filler dispersion and poor compatibility with the matrix, and are often non-continuous fiber-reinforced composites with relatively small driving strain. Other preparation methods include Chinese patent CN201511018878.9, which uses random copolymerization to prepare a polyimide / carbon fiber hybrid film containing carbon fibers, achieving electrically driven shape memory functionality. Chinese patent CN201911282157.7 describes a method for preparing a grid template on a rigid substrate, depositing a double-layer metal film on the surface, removing the grid template to obtain a metal grid protruding on the substrate surface, and further coating the surface with a shape memory polymer to obtain an embedded double-layer metal grid conductive film. Chinese patent CN2021103317634 describes an electrically driven continuous carbon fiber reinforced shape memory polymer deformable skin with designable resistance, which is achieved by coating the shape memory polymer matrix on the outside of continuous carbon fibers. Compared with simply filling particles or short fibers, its mechanical properties are further improved. These methods improve the electrical and thermal conductivity of composite materials, but there are still some problems: Specifically, (1) Currently, many electrically driven shape memory composite materials have insufficient deformation and recovery rates and high driving voltages. It is necessary to seek to prepare electrically driven shape memory polymers reinforced with continuous fibers to obtain the effects of large deformation, fast recovery, and low driving voltage. (2) It is necessary to find a conductive matrix or conductive pathway with better performance to obtain a composite material with simple preparation method and better electrical and thermal conductivity.
[0004] Furthermore, combining electric drive with bidirectional shape memory, as a more practical material, can undoubtedly further broaden the scope of application and application fields of shape memory materials. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide an electrically driven bidirectional shape memory polyimide composite fiber cloth and its preparation method, so as to overcome the defects of the prior art in electrically driven shape memory polymers, such as small deformation, complicated preparation, insufficient electrical and thermal conductivity, high driving voltage, and slow deformation recovery.
[0006] This invention provides an electrically driven bidirectional shape memory polyimide composite fiber fabric, woven from warp and weft yarns. The weft yarn is an aromatic polyimide fiber, and the warp yarn is a blend of aromatic polyimide fiber and conductive fiber. Conductive pathways are engraved on one side of the polyimide composite fiber fabric, and a thermoplastic shape memory polyimide film is hot-pressed onto the same side.
[0007] Preferably, the aromatic polyimide fiber is a commercially available polyimide fiber with high temperature resistance, high strength and high modulus properties, and is preferably selected from one or more of Suplon, high strength and high modulus fiber and Fitlon from Jiangsu Aoshen New Material Co., Ltd.
[0008] Preferably, the weft yarn raw material is 100% aromatic polyimide fiber by weight percentage.
[0009] Preferably, the warp yarn raw material is: 93-99% aromatic polyimide fiber and 1-7% conductive fiber by weight percentage.
[0010] Preferably, the conductive fiber comprises alloy fiber and / or carbon fiber.
[0011] Preferably, the alloy fibers include nickel-chromium alloy fibers and / or iron-chromium-aluminum alloy fibers; the conductive fiber diameter is 20~80μm.
[0012] Preferably, the shape of the conductive path includes a folded linear shape or a striped shape.
[0013] Preferably, the thermoplastic shape memory polyimide film has one or more of the following shapes: quadrilateral, grid, wavy, circular, and gate-shaped, and its thickness is 5~200μm.
[0014] This invention also provides a method for preparing an electrically driven bidirectional shape memory polyimide composite fiber fabric, comprising:
[0015] (1) A fabric is woven using aromatic polyimide fiber as the weft yarn and a blended yarn of aromatic polyimide fiber and conductive fiber as the warp yarn. A conductive path is drawn on one side of the fiber fabric by laser engraving.
[0016] (2) Hot-press thermoplastic shape memory polyimide film on the same side and coat it onto the surface of the fiber cloth to obtain an electrically driven bidirectional shape memory polyimide composite fiber cloth.
[0017] Preferably, the fabric woven in step (1) is a woven, machine-woven, knitted or woven fabric with warp and weft yarns interlaced, and the fabric structure is plain weave, satin weave, twill weave or warp knit, with warp and weft yarn densities of (300~600)×(300~600) yarns / 10cm.
[0018] Preferably, the laser engraving process parameters in step (1) are: the laser engraving distance (distance between the laser source and the fiber cloth) is 40~75mm, the laser power is 6~9.5 W, and the engraving speed is 5~30mm / s.
[0019] Preferably, the hot pressing process parameters in step (2) are: hot pressing temperature of 230~350℃, heating rate of 5~15℃ / min, pressure of 3~15MPa, and time of 20~80min.
[0020] Preferably, the method for preparing the thermoplastic shape memory polyimide film in step (2) includes:
[0021] Dianone and diamine are added to a solvent at a molar ratio of 1 to 1.05:1 and reacted at 190 to 210°C for 10 to 15 hours. After cooling, a film is laid on a substrate and heat-treated in a vacuum oven. After treatment, the film is removed to obtain the product. The total mass of diamine and dianone accounts for 5 to 20% of the total mass of diamine, dianone and solvent.
[0022] Preferably, the dianhydride comprises: , , , , One or more of them.
[0023] Preferably, the diamine comprises , , , , , , One or more of them.
[0024] Preferably, the solvent is N-methylpyrrolidone (NMP).
[0025] Preferably, the substrate comprises one or more of polytetrafluoroethylene plates, glass sheets, and silicon wafers.
[0026] Preferably, the heat treatment process parameters are as follows: heating to 50-80℃ at a rate of 2-3℃ / min, holding at that temperature for 60-90 hours; heating to 100-120℃ at a rate of 10-15℃ / min, holding at that temperature for 1-2 hours; heating to 200-220℃ at a rate of 10-15℃ / min, holding at that temperature for 1-2 hours; heating to 300-320℃ at a rate of 10-15℃ / min, holding at that temperature for 1-2 hours; and finally cooling to 30℃ at a rate of 2-4℃.
[0027] Preferably, the demolding process involves immersing the thermoplastic shape memory polyimide in deionized water until the film detaches from the substrate.
[0028] This invention also provides an application of electrically driven bidirectional shape memory polyimide composite fiber fabric in functional textiles, space-deployable structures, flexible electronic devices, or defense and military industries.
[0029] This invention relates to a fiber fabric in which conductive and heat-generating fibers are blended into the warp yarns, serving as the first conductive component for efficient heat generation. A conductive pathway, laser-engraved on one side, serves as the second conductive component. It should be noted that while other fibers are blended into the warp yarns to form conductive pathways, the weft yarns are polyimide fibers. In this case, the warp yarns are arranged in parallel, and the low-content conductive fibers are randomly distributed among the fibers, making it difficult to form pathways. By laser-engraving folded linear conductive pathways on the surface, the first conductive component's conductive pathways, which are in a broken state, can be connected. Simultaneously, it repairs defects in the first conductive component caused by breakage of conductive fibers during use. The large-area carbonized surface can conduct the heat generated by the first conductive component to the entire composite fiber fabric. The combination of the first and second conductive components achieves designability of the conductive pathways, high efficiency in conductivity-heat generation-heat conduction, and a simple preparation method. When powered on, the laser-carbonized polyimide fibers generate heat, and the modulus of the thermoplastic shape memory polyimide film decreases upon heating. This triggers the polyimide fiber cloth, which stores bending potential energy, to pull the sample back to its permanent shape, i.e., a relatively flat state. When powered off, the laser-carbonized polyimide fibers dissipate heat, and the elastic modulus of the shape memory polyimide polymer molecular chains increases, pulling the polyimide fiber cloth to bend. The sample returns to a temporary curled shape while storing bending potential energy. By repeating this process, the sample is electrically driven to achieve a cyclical transformation between permanent and temporary shapes.
[0030] The shape memory polyimide polymer film of the present invention has excellent shape memory properties, adjustable driving temperature, and glass transition temperature between 230 and 360°C. After hot pressing, it is coated on the surface of polyimide composite fiber cloth. Based on the principle of polymer properties and structure, it is tightly connected with the polyimide composite fiber cloth through intermolecular forces. With the cooperation of the first conductive component and the second component electrothermal generation, an electrically driven polyimide composite fiber cloth with bidirectional shape memory function is constructed.
[0031] Beneficial effects
[0032] (1) The present invention is simple and efficient. The electrically driven bidirectional shape memory polyimide composite fiber cloth prepared has excellent mechanical, thermal and electrical properties. The deformation temperature is adjustable in a large temperature range (shape memory polyimide Tg±20℃), filling the gap in the field of electrically driven bidirectional shape memory polyimide composite fiber cloth.
[0033] (2) The electrically driven bidirectional shape memory polyimide composite fiber fabric prepared by this invention has large shape memory deformation, can be remotely controlled, has a fast response, strong controllability, and low driving voltage. Under a DC voltage of 15V, the heat conduction time is 3s and the response time is 20s.
[0034] (3) The bidirectional shape memory polyimide composite fiber fabric prepared by the present invention has a shape memory transition temperature of 230~360℃. After 10 cycles, the bidirectional shape recovery rate is >95% and the bidirectional bending shape strain is greater than or equal to 52%, which has excellent shape memory thermal cycling stability. Attached Figure Description
[0035] Figure 1 These are schematic diagrams (a) and physical images (b) of the electrically driven bidirectional shape memory polyimide composite fiber cloth of the present invention.
[0036] Figure 2 The diagram shows the composite fiber fabric of the present invention (a), the laser-engraved fold lines (b) and (c), and the horizontal lines (d).
[0037] Figure 3 The shape changes of the electrically driven bidirectional shape memory polyimide composite fiber cloth prepared in Example 2 of this invention during the shape memory cycle are shown in the following figures: a) initial shape; b) shape after 20 seconds of power-on at a rated DC voltage of 15V; c) shape after power-off; d) shape after 20 seconds of power-on at a rated voltage of 15V after 10 cycles; and e) shape after power-off after 10 cycles. Detailed Implementation
[0038] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0039] Raw materials: polyimide fiber, purchased from Jiangsu Aoshen New Material Co., Ltd.; dianhydride, diamine and N-methylpyrrolidone (NMP) were purchased from Sinopharm.
[0040] Mechanical properties were measured using an Instron (5956) at a stress loading rate of 10 mm / min and a spline size of 5 × 80 mm.
[0041] Thermal stability was measured by TGA (Netzsch) at a heat flow rate of 10℃ / min under a nitrogen atmosphere, with a sample size of 5~10mg.
[0042] The thermal conductivity of the composite fiber sample surface was characterized using an infrared camera FLIR-T460. After power-on, the time from the start of heating to the point where the fiber surface temperature no longer changed significantly within 3 seconds was recorded as the time for heat conduction on the sample surface.
[0043] After power is applied, a stopwatch is used to record the time it takes for the composite fiber to transition between a temporary and a permanent shape. The time for shape recovery / setting is taken as the point at which the shape of the composite fiber no longer changes within 3 seconds, as observed by the human eye.
[0044] The bending deformation rate and bending recovery rate of electrically driven bidirectional shape memory polyimide composite fiber fabric are calculated as follows:
[0045] The sample to be tested was cut into strips of 50×30mm;
[0046] R ε弯曲 =(L 永久 -L 临时 ) / L 永久 ×100
[0047] Where: R ε弯曲 : Bending deformation rate
[0048] L 临时 When the spline is in a temporary shape, the distance between the curled end and the two ends of the spline diagonal;
[0049] L 永久 When the spline is in a permanent shape, the distance between the curled end and the two ends of the spline diagonal;
[0050] R r =(L n,永久 - Ln,临时 ) / (L n,永久 - L n-1,临时 ) x100
[0051] Where: R r Bending deformation recovery rate
[0052] L n,临时 : In the nth (in this test, n=10, the same below) cycle, when the spline is in a temporary shape, the distance between the curled end and the two ends of the spline diagonal;
[0053] L n,永久 : In the nth cycle, when the spline is in a permanent shape, the distance between the curled end and the two ends of the spline diagonal;
[0054] L n-1,永久 : In the (n-1)th cycle, when the spline is in a permanent shape, the distance between the curled end and the two ends of the spline diagonal.
[0055] The preparation method of the thermoplastic shape memory polyimide polymer liquid in the example is as follows: 8.8848 g (0.02 mol) of 4,4'-(hexafluoroisopropene)phthalic anhydride and 10.3690 g (0.02 mol) of 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane were added sequentially to a three-necked flask containing 109.11 g of N-methylpyrrolidone (NMP). The reaction was carried out under a nitrogen atmosphere at 200 °C for 12 h, and then cooled to room temperature for later use. The main indicator is: the weight average molecular weight is 30 kg / mol to 50 kg / mol as determined by gel permeation chromatography.
[0056] Example 1
[0057] (1) Take 15 ml of the above polymerization solution and spread it horizontally on the surface of a 10×10 cm glass plate. In a vacuum oven, heat the solution to 60°C at a rate of 3°C / min and keep it at that temperature for 72 h. Heat the solution to 100°C, 200°C and 300°C at a rate of 15°C / min and keep it at that temperature for 1 h. Finally, cool the solution to 30°C at a rate of 2°C / min. Immerse the substrate in deionized water until the film separates from the substrate. Dry the substrate in a forced-air oven at 90°C for later use.
[0058] (2) The blended fibers were woven into a fabric with a plain weave structure and a warp and weft density of 450×450 yarns / 10cm. The weight percentage of the weft raw materials was 100% Suplon type fiber, and the weight percentage of the warp raw materials was 96% Suplon type fiber and 4% nickel-chromium alloy fiber. The diameter of the nickel-chromium alloy fiber was 40μm. A 50×30mm sample of the composite fiber fabric was cut out, and a folded linear pattern was laser-engraved on the upper surface. The laser engraving distance (distance between the laser source and the fiber fabric) was 50mm, the light intensity was 7.5w, and the speed was 5mm / s. After laser engraving, the polyimide composite fiber fabric had a sheet resistance of 1.9Ω / sq, exhibiting excellent electrical conductivity.
[0059] (3) Cut the film from step (1) into 50×30mm samples, place them on the laser-engraved side of the composite fiber cloth, and hot-press for 40 minutes to set the shape. The hot-pressing temperature is 320℃, the heating rate is 10℃ / min, and the pressure is 7MPa. Then, electrically drive the bidirectional shape memory polyimide composite fiber cloth. The fiber cloth has a tensile strength of 1.7GPa, a tensile modulus of 86GPa, and a 5% weight loss temperature of 608℃, indicating that the material has good high-temperature resistance.
[0060] After applying a 15V DC voltage for 3 seconds, the surface temperature of the composite fiber cloth rose to 260℃; after 21 seconds of power-on, the bending deformation rate reached 68%; after 15 seconds of power-off, the fiber cloth recovered its shape and the deformation was stable; after 10 rounds of electric drive bidirectional shape memory cycle test (applying and disconnecting DC voltage sequentially, 10 cycles), the bending deformation rate of the polyimide composite fiber cloth reached 68%, and the shape recovery rate reached 98%.
[0061] Example 2
[0062] (1) Take 15 ml of the above polymerization solution and spread it horizontally on the surface of a 10×10 cm glass plate. In a vacuum oven, heat the solution to 60°C at a rate of 3°C / min and keep it at that temperature for 72 h. Heat the solution to 100°C, 200°C and 300°C at a rate of 15°C / min and keep it at that temperature for 1 h. Finally, cool the solution to 30°C at a rate of 2°C / min. Immerse the substrate in deionized water until the film separates from the substrate. Dry the substrate in a forced-air oven at 90°C for later use.
[0063] (2) Preparation method and laser engraving process parameters of blended fiber fabric: As in Example 1, the laser engraving speed was changed to 10 mm / s, and the rest were the same as in Example 1. After laser engraving, the sheet resistance of the polyimide composite fiber fabric was 2.7 Ω / sq, which has excellent electrical conductivity.
[0064] (3) Cut the film from step (1) into 50×30mm samples, place them on the laser-engraved side of the composite fiber cloth, and hot-press for 40 minutes to set the shape. The hot-pressing temperature is 320℃, the heating rate is 10℃ / min, and the pressure is 7MPa. Then, electrically drive the bidirectional shape memory polyimide composite fiber cloth. The fiber cloth has a tensile strength of 2.3GPa, a tensile modulus of 99GPa, and a 5% weight loss temperature of 614℃, indicating that the material has good high-temperature resistance.
[0065] After applying a 15V DC voltage for 3 seconds, the surface temperature of the composite fiber cloth rose to approximately 260℃; Figure 3 As can be seen from AC, after 20 seconds of energization, the bending deformation rate reached 70%, and after 14 seconds of de-energization, the fiber cloth recovered its shape and the deformation stabilized; from Figure 3 After 10 rounds of electric-driven bidirectional shape memory cycle testing, the polyimide composite fiber fabric achieved a bending deformation rate of 70% and a shape recovery rate of 99%.
[0066] Example 3
[0067] (1) Take 15 ml of the above polymerization solution and spread it horizontally on the surface of a 10×10 cm glass plate. In a vacuum oven, heat the solution to 60°C at a rate of 3°C / min and keep it at that temperature for 72 h. Heat the solution to 100°C, 200°C and 300°C at a rate of 15°C / min and keep it at that temperature for 1 h. Finally, cool the solution to 30°C at a rate of 2°C / min. Immerse the substrate in deionized water until the film separates from the substrate. Dry the substrate in a forced-air oven at 90°C for later use.
[0068] (2) The preparation method and laser engraving process parameters of the blended fiber fabric were the same as in Example 2, except that the laser engraving speed was changed to 25 mm / s. The rest were the same as in Example 2. After laser engraving, the sheet resistance of the polyimide composite fiber fabric was 6.9 Ω / sq, which showed good electrical conductivity.
[0069] (3) Cut the film from step (1) into 50×30mm samples, place them on the laser-engraved side of the composite fiber cloth, and hot-press for 40 minutes to set the shape. The hot-pressing temperature is 320℃, the heating rate is 10℃ / min, and the pressure is 7MPa. Electric drive the bidirectional shape memory polyimide composite fiber cloth. The fiber cloth has a tensile strength of 2.6GPa, a tensile modulus of 112GPa, and a 5% weight loss temperature of 621℃. The material has good high-temperature resistance.
[0070] After applying a DC 15V voltage for 5 seconds, the surface temperature of the composite fiber cloth rises to about 260℃; after 31 seconds of power-on, the bending deformation rate reaches 50%; after 21 seconds of power-off, the fiber cloth recovers its shape and the deformation is stable; after 10 rounds of electric drive bidirectional shape memory cycle test, the bending deformation rate of the polyimide composite fiber cloth reaches 52% and the shape recovery rate reaches 97%.
[0071] Example 4
[0072] (1) Take 15 ml of the above polymerization solution and spread it horizontally on the surface of a 10×10 cm glass plate. In a vacuum oven, heat the solution to 60°C at a rate of 3°C / min and keep it at that temperature for 72 h. Heat the solution to 100°C, 200°C and 300°C at a rate of 15°C / min and keep it at that temperature for 1 h. Finally, cool the solution to 30°C at a rate of 2°C / min. Immerse the substrate in deionized water until the film separates from the substrate. Dry the substrate in a forced-air oven at 90°C for later use.
[0073] (2) The preparation method and laser engraving process parameters of the blended fiber fabric were the same as in Example 2, except that the laser engraving intensity was changed to 6.5W. The rest were the same as in Example 2. After laser engraving, the sheet resistance of the polyimide composite fiber fabric was 3.1Ω / sq, which showed excellent conductivity.
[0074] (3) Cut the film from step (1) into 50×30mm samples, place them on the laser-engraved side of the composite fiber cloth, and hot-press for 40 minutes to set the shape. The hot-pressing temperature is 320℃, the heating rate is 10℃ / min, and the pressure is 7MPa. The bidirectional shape memory polyimide composite fiber cloth is then electrically driven. The fiber cloth has a tensile strength of 2.4GPa, a tensile modulus of 100GPa, and a 5% weight loss temperature of 614℃, indicating that the material has good high-temperature resistance.
[0075] After applying a DC 15V voltage for 3 seconds, the surface temperature of the composite fiber cloth rises to about 260℃; after 18 seconds of power-on, the bending deformation rate reaches 67%; after 14 seconds of power-off, the fiber cloth recovers its shape and the deformation is stable; after 10 rounds of electric drive bidirectional shape memory cycle test, the polyimide composite fiber cloth achieves a bending deformation rate of 67% and a recovery rate of 99%.
[0076] Example 5
[0077] (1) The method for preparing shape memory polyimide film is the same as in Example 2, except that the amount of polyimide polymer solution is changed to 10 ml.
[0078] (2) The blended fibers were woven into a fabric with a plain weave structure and a warp and weft density of 450×450 yarns / 10cm. The weight percentage of the weft raw materials was 100% Suplon type fiber, and the weight percentage of the warp raw materials was 96% Suplon type fiber and 4% nickel-chromium alloy fiber. The diameter of the nickel-chromium alloy fiber was 40μm. A 50×30mm composite fiber fabric sample was cut out, and a folded linear pattern was laser-engraved on the upper surface. The laser engraving distance (distance between the laser source and the fiber fabric) was 50mm, the light intensity was 7.5w, and the speed was 10mm / s. After laser engraving, the polyimide composite fiber fabric had a sheet resistance of 2.5Ω / sq, exhibiting excellent electrical conductivity.
[0079] (3) Cut the film from step (1) into 50×30mm samples, place them on the laser-engraved side of the composite fiber cloth, and hot-press for 40 minutes to set the shape. The hot-pressing temperature is 320℃, the heating rate is 10℃ / min, and the pressure is 7MPa. The bidirectional shape memory polyimide composite fiber cloth is then electrically driven. The fiber cloth has a tensile strength of 2.3GPa, a tensile modulus of 101GPa, and a 5% weight loss temperature of 612℃, indicating that the material has good high-temperature resistance.
[0080] After applying a DC 15V voltage for 4 seconds, the surface temperature of the composite fiber cloth rises to about 260℃; after 23 seconds of power-on, the bending deformation rate reaches 62%; after 14 seconds of power-off, the fiber cloth recovers its shape and the deformation is stable; after 10 rounds of electric drive bidirectional shape memory cycle test, the polyimide composite fiber cloth achieves a bending deformation rate of 62% and a recovery rate of 99%.
[0081] Example 6
[0082] (1) Take 15 ml of the above polymerization solution and spread it horizontally on the surface of a 10×10 cm glass plate. In a vacuum oven, heat the solution to 60°C at a rate of 3°C / min and keep it at that temperature for 72 h. Heat the solution to 100°C, 200°C and 300°C at a rate of 15°C / min and keep it at that temperature for 1 h. Finally, cool the solution to 30°C at a rate of 2°C / min. Immerse the substrate in deionized water until the film separates from the substrate. Dry the substrate in a forced-air oven at 90°C for later use.
[0083] (2) Preparation method of blended fiber cloth and laser engraving process parameters: According to Example 1, the weight percentage of warp yarn raw materials was changed to: 99% Suplon type fiber and 1% nickel-chromium alloy fiber; after laser engraving, the sheet resistance of polyimide composite fiber cloth was 2.7Ω / sq, which has excellent conductivity.
[0084] (3) Cut the film from step (1) into 50×30mm samples, place them on the laser-engraved side of the composite fiber cloth, and hot-press for 40 minutes to set the shape. The hot-pressing temperature is 320℃, the heating rate is 10℃ / min, and the pressure is 7MPa. Then, electrically drive the bidirectional shape memory polyimide composite fiber cloth. The fiber cloth has a tensile strength of 2.3GPa, a tensile modulus of 99GPa, and a 5% weight loss temperature of 614℃, indicating that the material has good high-temperature resistance.
[0085] After applying a DC 15V voltage for 7 seconds, the surface temperature of the composite fiber cloth rises to about 260℃; after 31 seconds of power-on, the bending deformation rate reaches 58%; after 22 seconds of power-off, the fiber cloth recovers its shape and the deformation is stable; after 10 rounds of electric drive bidirectional shape memory cycle test, the polyimide composite fiber cloth achieves a bending deformation rate of 58% and a recovery rate of 98%.
[0086] Comparative Example 1
[0087] (1) Take 15 ml of the above polymerization solution and spread it horizontally on the surface of a 10×10 cm glass plate. In a vacuum oven, heat the solution to 60°C at a rate of 3°C / min and keep it at that temperature for 72 h. Heat the solution to 100°C, 200°C and 300°C at a rate of 15°C / min and keep it at that temperature for 1 h. Finally, cool the solution to 30°C at a rate of 2°C / min. Immerse the substrate in deionized water until the film separates from the substrate. Dry the substrate in a forced-air oven at 90°C for later use.
[0088] (2) Preparation method of blended fiber cloth and laser engraving process parameters: According to Example 1, the weight percentage of warp yarn raw materials was changed to: 100% Suplon type fiber and 0% nickel-chromium alloy fiber; after laser engraving, the sheet resistance of polyimide composite fiber cloth was 2.6Ω / sq, which has excellent conductivity.
[0089] (3) Cut the film from step (1) into 50×30mm samples, place them on the laser-engraved side of the composite fiber cloth, and hot-press for 40 minutes to set the shape. The hot-pressing temperature is 320℃, the heating rate is 10℃ / min, and the pressure is 7MPa. The bidirectional shape memory polyimide composite fiber cloth is then electrically driven. The fiber cloth has a tensile strength of 2.0GPa, a tensile modulus of 94GPa, and a 5% weight loss temperature of 605℃, indicating that the material has good high-temperature resistance.
[0090] After applying a DC 15V voltage for 8 seconds, the surface temperature of the composite fiber cloth rose to about 260℃; after 35 seconds of power-on, the bending deformation rate reached 56%; after 24 seconds of power-off, the fiber cloth recovered its shape and the deformation was stable; after 10 rounds of electric drive bidirectional shape memory cycle test, the polyimide composite fiber cloth achieved a bending deformation rate of 56% and a recovery rate of 92%.
[0091] Comparative Example 2
[0092] (1) Take 15 ml of the above polymerization solution and spread it horizontally on the surface of a 10×10 cm glass plate. In a vacuum oven, heat the solution to 60°C at a rate of 3°C / min and keep it at that temperature for 72 h. Heat the solution to 100°C, 200°C and 300°C at a rate of 15°C / min and keep it at that temperature for 1 h. Finally, cool the solution to 30°C at a rate of 2°C / min. Immerse the substrate in deionized water until the film separates from the substrate. Dry the substrate in a forced-air oven at 90°C for later use.
[0093] (2) The method for preparing the blended fiber fabric is the same as in Example 1, but without laser engraving; the sheet resistance of the composite fiber fabric is 6.2 x 10⁻⁶. 4 Ω / sq, poor electrical conductivity.
[0094] (3) Cut the film from step (1) into 50×30mm samples, place them on one side of the composite fiber cloth, and hot-press for 40 minutes to set the shape. The hot-pressing temperature is 320℃, the heating rate is 10℃ / min, and the pressure is 7MPa. Electric drive the bidirectional shape memory polyimide composite fiber cloth. The fiber cloth has a tensile strength of 2.9GPa, a tensile modulus of 117GPa, and a 5% weight loss temperature of 631℃. The material has good high-temperature resistance.
[0095] Since no conductive path is formed on the surface of the fiber cloth, no heat is generated on the surface of the composite fiber cloth when a DC voltage is applied, and it does not have electrically driven shape memory properties.
Claims
1. An electrically driven bidirectional shape memory polyimide composite fiber fabric, woven from warp and weft yarns, characterized in that, The weft yarn is an aromatic polyimide fiber, and the warp yarn is a blend of aromatic polyimide fiber and conductive fiber. Conductive pathways are engraved on one side of the polyimide composite fiber fabric, and a thermoplastic shape memory polyimide film is hot-pressed onto the same side.
2. The electrically driven bidirectional shape memory polyimide composite fiber fabric according to claim 1, characterized in that, The weft yarn raw material is 100% aromatic polyimide fiber by weight percentage; the warp yarn raw material is 93-99% aromatic polyimide fiber and 1-7% conductive fiber by weight percentage.
3. The electrically driven bidirectional shape memory polyimide composite fiber fabric according to claim 1, characterized in that, The conductive fiber includes alloy fiber and / or carbon fiber; the alloy fiber includes nickel-chromium alloy fiber and / or iron-chromium-aluminum alloy fiber; the diameter of the conductive fiber is 20~80μm.
4. The electrically driven bidirectional shape memory polyimide composite fiber fabric according to claim 1, characterized in that, The conductive path shape includes folded linear or striated shapes; the thermoplastic shape memory polyimide film shape includes one or more of the following: quadrilateral, grid, wavy, circular, and gate-shaped, with a thickness of 5~200μm.
5. A method for preparing an electrically driven bidirectional shape memory polyimide composite fiber fabric, comprising: (1) A fabric is woven using aromatic polyimide fiber as the weft yarn and a blended yarn of aromatic polyimide fiber and conductive fiber as the warp yarn. A conductive path is drawn on one side of the fiber fabric by laser engraving. (2) Hot-press thermoplastic shape memory polyimide film on the same side and cover the surface of the fiber cloth to obtain an electrically driven bidirectional shape memory polyimide composite fiber cloth.
6. The preparation method according to claim 5, characterized in that, In step (1), the fabric is woven by weaving warp and weft yarns into a woven, machine-woven, knitted or woven fabric. The fabric structure is plain weave, satin weave, twill weave or warp knit, and the warp and weft yarn density is (300~600)×(300~600) yarns / 10cm.
7. The preparation method according to claim 5, characterized in that, The laser engraving process parameters in step (1) are: the distance between the laser source and the fiber cloth is 40~75mm, the laser power is 6~9.5 W, and the engraving speed is 5~30mm / s.
8. The preparation method according to claim 5, characterized in that, The hot pressing process parameters in step (2) are: hot pressing temperature is 230~350℃, heating rate is 5~15℃ / min, pressure is 3~15MPa, and time is 20~80min.
9. The application of the electrically driven bidirectional shape memory polyimide composite fiber fabric as described in claim 1 in functional textiles, space-deployable structures, flexible electronic devices, or defense and military industries.
Citation Information
Patent Citations
Preparation method of electrically-driven shape memory polyimide
CN105542205A
Shape memory embedded double-layer metal grid conducting film and preparation method thereof
CN110838386A
Bidirectional shape memory polyimide fiber cloth and preparation method thereof
CN113417145A
Aramid fiber and polyimide different-warp double-layer fabric and weaving process thereof
CN114592262A